Studi dan Karakterisasi Bahan Baku Resorsinol sebagai calon Baku Pembanding dan Pengembangan Metode Analisis Penetapan Kadar Resorsinol dalam Bahan Baku - Isnaeni, Neni; Dwirini, Nurul (Eruditio : Indonesia Journal of Food and Drug Safety, 2023)
Resorcinol is often misused for antiacne cosmetics. Corresponding to Indonesian FDA regulation, it is only allowed for hair dyes, hair lotion, and shampoo. Reference standard and analytical method of Resorcinol are needed for strengthening capability and capacity of Indonesian FDA for post-market controlling of cosmetics in Indonesia. Therefore, this research developed a reference standard by study and characterization and an analytical method for assay Resorcinol in raw material. Characterization of Resorcinol raw material using infrared spectrophotometry and HPLC-PDA, purity testing with TLC, HPLC, and DSC, homogeneity testing and assay by HPLC-PDA. Development analytical method for assay of Resorcinol was performed using an HPLC - PDA system with Waters Atlantis T3-C18 (5µm, 250 x 4.6 mm) column. The column temperature was set at 25°C. The mobile phase consists of ortho-phosphoric acid 0.085% pH 3 and methanol (50:50 v/v), delivered at a 1.0 mL/min flow rate. Detection was carried out at 274 nm. Resorcinol characterization using infrared spectrophotometry showed the presence of aromatic C-H bond functional groups (3100 – 3000 cm-1), C-H bonds (1374 and 773 cm-1), C-OH bonds (1311-1298, 1166; 1151 and 460 cm-1), C-C bonds (1608 and 1490 cm-1), aromatic rings (543 cm-1), and meta di-substituted ring groups (842 and 739 cm-1). Purity testing by TLC and HPLC were obtained that no spots or other peaks detected, indicating that the material has high purity. Purity by DSC of 99.05% and melting point of 109.41°C. The sample was homogenous with a content of 99.28% on a dried basis. Furthermore, the developed method has a linear range of 0.1 – 0.3 mg/mL at a coefficient correlation of 0.9999 and Vx0 of 0.5%. The limit of detection is 0.11 µg/mL, while the limit of quantification is 0.34 µg/mL and accuracy (% bias) of 0.10%. All validation parameters have met the requirement. These results meet the criteria for the candidate of a reference standard and the developed method is accurate, reliable, and valid so it can be applied to determine Resorcinol in raw material.